update zkp for dec(c) = 0

update-fork
MITSUNARI Shigeo 4 years ago
parent 4407af6e33
commit 27f51cb987
  1. 52
      misc/she/memo.txt

@ -31,18 +31,46 @@ Bi := d Pi - h Ai
verify h = Hash(P2, A1, A2, B1, B2)
-----------------------------------------------------------------------------
CipherTextGT
P ; generator of GT
P ; generator of GT, GT=<P>
x1, x2 ; secrect key
(P0, P1, P2, P3) := (P, x1 P, x2 P, x1 x2 P) ; public information
CipherText c = (A0, A1, A2, A3)
dec(c) = 0 <=> A0 = x2 A1 + x1 A2 - x1 x2 A3 ; (*)
construction of ZKP for dec(c) = 0, i.e., show (*)
F(a1, a2, a3) := a2 A1 + a1 A2 - a3 A3
dec(c) = 0 <=> A0 = F(x1, x2, x1 x2)
Sigma-protocol for dec(c) = 0, i.e., show (*)
Prover:
b1, b2, b3 ; rand
Bi := bi P (i = 1, 2, 3)
X := F(b1, b2, b3)
send (B1, B2, B3, X) to Verfier
Verifier:
takes h randomly and send to Prover
Prover:
d1 := b1 + h x1
d2 := b2 + h x2
d3 := b3 + h x1 x2
send (d1, d2, d3) to Verifier
Verifier:
verify
di P = Bi + h Pi (i = 1, 2, 3)
X = F(d1, d2, d3) - h A0
and accept it
Fiat-Shamir transform:
Prover:
b1, b2, b3 ; random value
Bi := bi P for i = 1, 2, 3
X := b1 A2 + b2 A1 - b3 A3
Bi := bi P (i = 1, 2, 3)
X := F(b1, b2, b3)
h := Hash(P0, ..., P3, A0, ..., A3, B1, B2, B3, X)
d1 := b1 + h x1
d2 := b2 + h x2
@ -52,7 +80,7 @@ pi := (d1, d2, d3, h)
Verifier:
(pi, {Pi}, {Ai}) given
Bi' := di P - h Pi for i = 1, 2, 3
X' := d1 A2 + d2 A1 - d3 A3 - h A0
X' := F(d1, d2, d3) - h A0
verify Hash({Pi}, {Ai}, {Bi'}, X') = h
Completeness
@ -60,8 +88,10 @@ Completeness
B1' = d1 P - h P1 = (b1 + h x1) P - h x1 P = b1 P = B1
B2' = d2 P - h P2 = (b2 + h x2) P - h x2 P = b2 P = B2
B3' = d3 P - h P3 = (b3 + h x1 x2) P - h x1 x2 P = B3
X' = (b1 + h x1) A2 + (b2 + h x2) A1 - (b3 + h x1 x2)A3 - h A0
= b1 A2 + b2 A1 - b3 A3 + h (x1 A2 + x2 A1 - x1 x2 A3 - A0) = b1 A2 + b2 A1 - b3 A3 = X
X' = F(b1 + h x1, b2 + h x2, b3 + h x1 x2) - h A0
= F(b1, b2, b3) + h F(x1, x2, x1 x2) - h A0
= F(b1, b2, b3) + h (F(x1, x2, x1 x2) - A0)
= F(b1, b2, b3) = X
OK
Soundness
@ -80,8 +110,10 @@ B1' = d1 P - h P1 = b1 P
B2' = b2 P
B3' = b3 P
Y := x1 A2 + x2 A1 - x1 x2 A3 - A0 ; unknown, but it is fixed
X' = b1 A2 + b2 A1 - b3 A3 + h Y
Y := F(x1, x2, x1 x2) - A0; unknown, but it is fixed
X' = F(d1, d2, d3) - h A0 = F(b1 + h x1, b2 + h x2, b3 + h x1 x2) - h A0
= F(b1, b2, b3) + h(F(x1, x2, x1 x2) - A0)
= F(b1, b2, b3) + h Y
Hash({Pi}, {Ai}, b1 P, b2 P, b3 P, b1 A2 + b2 A1 - b3 A3 + h Y) = h
Hash({Pi}, {Ai}, b1 P, b2 P, b3 P, F(b1, b2, b3) + h Y) = h
To found {b1, b2, b3, h} to hold this equation, Y must be 0.

Loading…
Cancel
Save